Fast motion estimation algorithms for video coding - Zhu, Shan. (2009)
Digital video has many advantages over its analog counterpart. For effective storage and delivery, digital video data is required to be encoded at a much higher compression ratio compared with that of still image compression owing to its temporal redundancies. Motion estimation is the key technique to substantially reduce such redundancies but requires fairly high computation. Since many practical video applications (e.g., video conferencing) require real time processing of video data, fast and accurate motion estimation is crucial to the processing speed and reconstructed image quality.